Evaluation of viability of arbuscular mycorrhiza fungi on wheat (Triticum aestivum) plant - SARITA; SINGH, NARENDER; CHUGH, RAKESH KUMAR; KUMAR, SUNIL; AGGARWAL, SUMIT KUMAR; KAUR, HARMANJOT; KUMAWAT, KAILASH CHAND; NABI, SAJAD UN (The Indian Journal of Agricultural Sciences, 2025)
Mycorrhiza is the most common type of symbiotic relationship that exists between fungi and plant roots. Arbuscular mycorrhizal fungi (AMF) plays significant role in plant development, improving soil structure, nutrient cycle and plant resilience to environmental challenges like drought and pathogens. The present study was carried out during 2020 and 2021 at Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana to evaluate the viability of different mycorrhizal fungi (Glomus mosseae, G. fasciculatum, G. hoi and G. intraradices) up to seven months after shoot removal. Mycorrhizal fungi were raised and maintained on wheat (Triticum aestivum L.) (variety WH-1105) roots in earthen pots and it was observed that the sporocarp population (4475) and mycorrhizal colonization (96%) were highest in G. fasciculatum. The results indicated that the significantly lowest viability was observed in G. intraradices (35.4%) and maximum in G. mosseae (40.1%) during 2020. During 2021, G. intraradices again demonstrated the lowest viability (32.9%), with G. hoi achieving the highest (39.2%). The viability of different mycorrhizal species was found inversely proportional to the period after shoot detachment. The findings emphasize the necessity for better inoculum management techniques to maintain AMF functionality in agricultural environments and the dependence of AMF viability on host association.